Pembangunan Sistem Ujian Daring pada Sekolah Menengah Atas berbasis Android (Studi Kasus : SMAN 3 Lamongan) - Rakha Fakhruddin; Achmad Arwan; Denny Sagita Rusdianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Public Senior High School 3 Lamongan is an educational institution or agency that organizes educational, teaching and learning activities, examinations, and/or training. To support the teaching-learning process and an effective and efficient examination process, a good examination system is needed. However, this school has several problems in the exam process such as the susceptibility of students to cheating because each student gets the same questions during the exam so that in the exam process students can cheat with friends. In addition, at these schools the teachers had difficulty analyzing the results of the exams to find out what number of questions we're often answered incorrectly by students which would later be used for discussions in class. Environmental problems also underlie this research, where the school in conducting exams for a year spent 234000 sheets of paper. To reduce these problems, an online exam system was built to manage the exam process and test results analysis with features for creating questions, conducting exams, analyzing exam results, and recap score. This system was developed based on android using a Codeigniter framework on the backend side while on the frontend side using native apps technology which uses the java language. This study resulted in 43 functional needs and 1 non-functional requirement. The test results on the system, namely the unit test produced a valid status on each path tested in 3 sample units, integration testing resulted in a valid status in 1 test case, validation testing resulted in a valid status on 43 requirements tested, and compatibility testing showed that the test status was a success. which means the system can run well on various Androids and meets compatibility aspects.